1995
DOI: 10.1175/1520-0442(1995)008<1086:tvsist>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Volcanic Signal in Surface Temperature Observations

Abstract: Climate records of the past 140 years are examined for the impact of major volcanic eruptions on surface temperature. After the low-frequency variations and El Niño/Southern Oscillation signal are removed, it is shown that for 2 years following great volcanic eruptions, the surface cools significantly by 0.1 °-0.2 oC in the global mean, in each hemisphere, and in the summer in the latitude bands 00_30 0 S and 00_30 0 N and by 0.3°C in the summer in the latitude band 30°-60 0 N. By contrast, in the first winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
274
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 392 publications
(296 citation statements)
references
References 44 publications
20
274
1
1
Order By: Relevance
“…These particles alter the albedo of the Earth, reflecting a fraction of sunlight back into space and thereby reducing the Earth's temperature. Based on six of the largest eruptions of between 1875 and 1991, Robock and Mao (1995) show that the cooling can be on the order of 0.1 to 0.2 • C.…”
Section: Introductionmentioning
confidence: 99%
“…These particles alter the albedo of the Earth, reflecting a fraction of sunlight back into space and thereby reducing the Earth's temperature. Based on six of the largest eruptions of between 1875 and 1991, Robock and Mao (1995) show that the cooling can be on the order of 0.1 to 0.2 • C.…”
Section: Introductionmentioning
confidence: 99%
“…The aerosol particles converted from the Pinatubo SO2 injection were suspended in the atmosphere for several years and caused the largest aerosol perturbation to the stratosphere in the twentieth century. The scattering and absorption of solar radiation and the absorption of terrestrial radiation by the Pinatubo aerosol largely disturbed the radiation balance of the atmosphere [Stenchikov et In previous studies [Angell, 1988;Mass and Portman, 1989;Robock and Mao, 1995], SOI and area-averaged SST over the eastern tropical Pacific were used to represent and measure the strength of ENSO events, and attention was paid to the area-averaged surface or atmospheric temperature changes following volcanic eruptions. Here we focus on the geographical distributions of the observed SAT and their seasonal characteristics over land during the 3 years •bllowing the Pinatubo eruption, together with the corresponding changes in SST over the eastern tropical Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…Some have suggested that decadal to interdecadal variability can be phase locked by external signals such as variations in solar radiation [ White el al., 1997] and volcanic eruptions [Robock and Mao, 1995].…”
Section: Introductionmentioning
confidence: 99%